Interpretive structural modeling of the implementation of the comprehensive scientific map of Iran - Bahram Akbari; Abouzar Alidadi Talkhestani; Mohammad Reza Navab Esfahani; Meysam Alipour (مدیریت راهبردی دانش سازمانی)
Purpose: The present study aims to present an "interpretive structural modeling of the implementation of the country's comprehensive scientific map." Identifying the dimensions and components of the implementation of the country's scientific map involves developing an implementation model for this map to purposefully implement knowledge management strategies.Methodology: This research is developmental and applied in terms of orientation so that by collecting various data from the subject literature and upstream documents, it presents a conceptual model for implementing the country's scientific map so it is developmental and on the other hand, by determining the relationship between the components of the conceptual model and their leveling, it provides the basis for prioritizing and applying the model practically, so it is used. The statistical population of the research includes experts and officials implementing the country's scientific map, from which a sample size of 20 people was purposefully selected, and their opinions were used in responding to the structural-interpretive equations.Findings: The final model has been developed in two layers and consists of 5 dimensions, including "human factors," "infrastructural factors," "management factors," "process factors," and "external factors." The first component, titled "Implementation requirements and considerations for realizing the country's comprehensive scientific map", includes three axes: attention and application of field considerations for implementing the country's comprehensive scientific map document, considering the approach and maturity levels in implementing the country's comprehensive scientific map, creating a mechanism and paying attention to the coherence, coordination and integration of measures in implementing the country's comprehensive scientific map; The second process is called culture building as one of the necessities for realizing the implementation of the country's scientific map document, which includes three axes: Promoting the scientific and research insight of all those related to the issue of implementing the country's scientific map at different organizational levels and ranks, which will have a significant impact on realizing culture building in accordance with the priorities and strategies of the comprehensive scientific map, Developing thinking as a strategic and necessary indicator for better support of the demands and missions requested in the comprehensive scientific map document, which will have a direct impact on the implementation of the country's comprehensive scientific map, Discourse building in the sense that until the issue of realizing the implementation of the country's scientific map is recognized as a common currency, the issue of culture building will not crystallize and as a result, the implementation of the country's scientific map will not be realized. The third component is empowerment for realizing the country's comprehensive scientific map, which is defined in two issues: The need to pay attention to empowerment and skill development in implementing the country's comprehensive scientific map, which should be included in many current organizational trainings, considering the goals stated in the comprehensive scientific map document. The issue of developing skills in implementation is in placement and implementation in various educational courses. Designing and implementing the foundation program for the country's comprehensive scientific map education, considering the new content produced as well as the approaches and strategies included in the map content, requires designing, compiling, and implementing educational courses and programs in the form of foundation courses, etc., so that the issue of realizing empowerment can properly occur in the process of implementing the scientific map document. The fourth effective component in realizing the implementation process, which has a key impact on implementing the comprehensive scientific map document, is innovation studies in implementation, defined in three axes: target sociology and ecosystem studies. The realization of the implementation of the country's comprehensive scientific map should be proportionate to the accurate understanding of the target community, which is researchers and intellectuals, and the interactions and relations of this community with various organizations as the main ecosystem of the audience of the comprehensive scientific map of the country should be put on the agenda. Governance, policy research, and innovation studies: In the process of implementing the country's comprehensive scientific map, innovation expansion strategies will not be implemented and implemented except with the support of detailed studies in the field of governance, policy research, and innovation, which is the result of serious attention from relevant stakeholders and researchers; Studies of integrated patterns of transformation and improvement, this issue has a significant impact on the implementation of the country's scientific map in line with developments inside and outside the organization's environment and keeping the country's comprehensive scientific map up-to-date with these developments, and as a result, the country's better synchronization with the realization of the map's goals; The fifth process, titled evaluation, supervision, and monitoring, is also one of the priorities for implementing the country's scientific map document, which includes three axes: Implementation status assessment, this process is achieved in implementing the country's comprehensive scientific map by following up and monitoring in the field the progress of programs and executive actions, and finally, implementation status assessment and forecasting of software platforms for continuous monitoring of the implementation of the country's comprehensive scientific map; The implementation of the implementation axes and feedback from it, including the implementation of an interactive feedback system and the use of lessons learned from the implementation of the document and its use in making optimal decisions, will be completed. Also, the pilot implementation of the Comprehensive Scientific Map of the Country document with the aim of corrective feedback before the implementation of the document; dynamism (counting improvement points) based on the results of the implementation, at this stage, in addition to the learning that is created as a result of monitoring and evaluation for those involved in the implementation of the Comprehensive Scientific Map of the Country document, counting strengths and usable lessons based on the results of the implementation seems necessary for better implementation of the document in the face of future challenges.Research limitations: This study's limitations included using self-report questionnaires to assess variables, limiting the research sample to teachers in Kashan, and conducting a cross-sectional study and collecting data.Originality/value: Identifying the factors affecting the governance and organization of the main components and elements of the science, technology, and innovation system, a model for implementing a comprehensive scientific map in Iran was presented clearly and precisely.